La Participación Ciudadana en la Gestión del Gobierno Autónomo Descentralizado del Cantón Paltas, periodo 2015 - Guamán Sandoval, Eddy Vinicio (2017)
3 SUMARY The present thesis aims at determining and analyzing the level of citizen participation in the management of the GAD of Paltas in 2015. This research was carried out by the nonconformity of the inhabitants in the efforts that the municipality has developed, for The importance of knowing if the opinion of the inhabitants has been taken into account in the management of the GAD. At present, it is very important the involvement of citizens in public management and even more so in municipal governments, because they are closer to their inhabitants, because that is where the best social, territorial and institutional context is found. Better coordination between the inhabitants and the GAD of Paltas, consequently improves democratization and there is a co-responsibility between the inhabitants and the municipality To determine and analyze the level of citizen participation in the management of the GAD, the citizen participation ladder was used; "Continuum of Citizen Participation of Guillen, Saenz, Badii, & Castillo" was contrasted with the results obtained and the mechanisms of citizen participation established in the Municipal Ordinance of Citizen Participation and Social Control. Subsequently, it was possible to show a low level of citizen participation, and the position of the villagers regarding the management of the Paltas GAD has been an object of consultation, there has been no active and consistent participation in decision making Of the management of the municipality.